Effect of buffer layer on thermal recovery of superconducting nanowire single-photon detector. (1st June 2021) - Xu, T; Chen, S; Shi, H K; Jia, X Q; Zhang, L B; Zhao, Q Y; Tu, X C; Kang, L; Chen, J; Wu, P H
Abstract: Superconducting nanowire single-photon detectors (SNSPDs) wherein ultrathin films are fabricated on Si substrates are greatly affected by lattice mismatch between the thin film and the substrate. A buffer layer can be used to reduce such lattice mismatch or optimize the strain in the film, thereby improving device performance. We prepared and optimized Nb5 N6 as a buffer layer and found that it considerably improved the properties of NbN films on Si substrates. The zero-resistance critical temperature ( T C0 ) of a 3 nm thick NbN film with a 20 nm thick buffer layer was 10.3 K. SNSPDs with Nb5 N6 -buffered NbN films were fabricated and compared with normal devices; the fabricated devices had high hysteresis current and low timing jitter. Furthermore, we investigated the thermal diffusion process of the device based on the hysteresis current and hotspot relaxation time and found that Nb5 N6 buffer layers enhance the thermal coupling between the superconducting film and substrates. The relaxation time of buffered SNSPD was 14.2 ps, which was shorter than that of nonbuffered SNSPD by 17.8 ps. These effects explain the performance improvement observed in the case of the buffered devices.